Immune checkpoint blockade in hematological malignancies: current state and future potential - Pophali, Prateek; Varela, Juan Carlos; Rosenblatt, Jacalyn (Frontiers in Oncology, 2024)
Malignant cells are known to evade immune surveillance by engaging immune checkpoints which are negative regulators of the immune system. By restoring the T-lymphocyte mediated anti-tumor effect, immune checkpoint inhibitors (ICI) have revolutionized the treatment of solid tumors but have met rather modest success in hematological malignancies. Currently, the only FDA approved indications for ICI therapy are in classic hodgkin lymphoma and primary mediastinal B cell lymphoma. Multiple clinical trials have assessed ICI therapy alone and in combination with standard of care treatments in other lymphomas, plasma cell neoplasms and myeloid neoplasms but were noted to have limited efficacy. These trials mostly focused on PD-1/PDL-1 and CTLA-4 inhibitors. Recently, there has been an effort to target other T-lymphocyte checkpoints like LAG-3, TIM-3, TIGIT along with improving strategies of PD-1/PDL-1 and CTLA-4 inhibition. Drugs targeting the macrophage checkpoint, CD47, are also being tested. Long term safety and efficacy data from these ongoing studies are eagerly awaited. In this comprehensive review, we discuss the mechanism of immune checkpoint inhibitors, the key takeaways from the reported results of completed and ongoing studies of these therapies in the context of hematological malignancies.